Characterization and in vivo assay of chitosan alginate microencapsulation to deliver the combination of HBcAg and HBsAg as a hepatitis B oral vaccine candidate - Nurlaili Ekawati; Nurlaili Ekawati; Mohamad Taufik; Apon Zaenal Mustopa; Ari Estuningtyas; Imelda Rosalyn Sianipar; Ai Hertati; Maritsa Nurfatwa; Djadjat Tisnadjaja; Tri Isyani Tungga Dewi (Faculty of Pharmacy, Mahidol University, 2022)
Chronic hepatitis B infection is one of main factors of cirrhosis primary cause, which can develop into hepatocellular carcinoma. Medically, there are various disadvantages associated with administering hepatitis B vaccine through injection, include pain, reduced patient compliance, higher production costs, and inadequate mass vaccination. Therefore, it is necessary to develop an oral vaccine. This study aims to develop and characterize oral vaccine through combination of Hepatitis B Surface Antigen (HBsAg) and Hepatitis B Core Antigen (HBcAg) encapsulated within chitosan alginate. The vaccine formula was prepared by ionic gelation method that consists of HBcAg (marked as MPS) and a combination of HBcAg and HBsAg (which is marked as MPC) microparticles. Examined parameters include loading efficacy, particle characteristics, anti-HBcAg immune response, ALT & AST, and liver histology. It was found that loading efficacy of MPS and MPC were 82.5±9.57 and 75.0±11.78%. The mean particle size (Z-average), polydispersity index (PdI), and zeta potential of MPS and MPC were 4,869±739 nm and 8,712±2,110 nm, 0.32±0.032 and 0.37±0.088, -7.50±1.82 mV and -2.10±1.59 mV, respectively. The Hepatitis B core antibody (HBcAb) started forming on the 35th day after first vaccination. The results show that both AST and ALT serum were in normal range. Therefore, antigen dose given in this study had no pathological effects on liver histology. Furthermore, based on its parameters such as loading efficacy, PdI, zeta potential, particle size, FTIR, and formation of HBcAb from the 35th day after vaccination, it concluded that combination of HBcAg and HBsAg is safely encapsulated within microparticles (MP) chitosan alginate.